2020
DOI: 10.1101/2020.03.22.20038919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of temperature and absolute humidity on the coronavirus disease 2019 (COVID-19) outbreak - evidence from China

Abstract: Background:The medical, health service, societal and economic impact of the COVID-19 emergency has unknown effects on overall population mortality. Previous models of population mortality are based on death over days among infected people, nearly all of whom (to date at least) have underlying conditions. Models have not incorporated information on high risk conditions or their longer term background (pre-COVID-19) mortality. We estimated the excess number of deaths over 1 year under different COVID-19 incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
178
1
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(203 citation statements)
references
References 45 publications
16
178
1
8
Order By: Relevance
“…Our findings thus indicate that globalized countries could have experienced multiple and recurrent introductions of the virus via imported goods, tourists, or international exchanges of students or academics (Anzai et al, 2020;Chinazzi et al, 2020). Importantly, local climate (represented by mean temperature, precipitation and vapor pressure) was not found associated with infection rates, supporting a recent study (Luo et al, 2020) and contradicting an evaluation from 31 provincial-level regions in mainland China (Shi et al, 2020) and a global analysis (Ficetola & Rubolini, 2020). The discrepancy between our results and those from Ficetola and Rubolini (2020) may be due to the fact that they calculated exponential growth rates over a period of five days, and assessed a more limited number of predictor variables.…”
Section: Discussioncontrasting
confidence: 67%
“…Our findings thus indicate that globalized countries could have experienced multiple and recurrent introductions of the virus via imported goods, tourists, or international exchanges of students or academics (Anzai et al, 2020;Chinazzi et al, 2020). Importantly, local climate (represented by mean temperature, precipitation and vapor pressure) was not found associated with infection rates, supporting a recent study (Luo et al, 2020) and contradicting an evaluation from 31 provincial-level regions in mainland China (Shi et al, 2020) and a global analysis (Ficetola & Rubolini, 2020). The discrepancy between our results and those from Ficetola and Rubolini (2020) may be due to the fact that they calculated exponential growth rates over a period of five days, and assessed a more limited number of predictor variables.…”
Section: Discussioncontrasting
confidence: 67%
“…Without effective interventions, the peak of epidemic will reach higher and the epidemic process will last longer [25]. Thus, the reproduction numbers will not decline until a large proportion of It has been suggested that like many other respiratory virus infections, a seasonal pattern may exist for SARS like coronavirus [26,27]. However, as demonstrated in this study, the association between reproduction number and temperature was deeply confounded by interventions and other external factors (including altitudes and humidity).…”
Section: Resultsmentioning
confidence: 85%
“…These empirical frameworks conflate location-specific characteristics -such as testing capacity, population density, and health services -with temperature variation. [8][9][10] Because temperature is correlated with many (often unobservable) confounding factors, such cross-sectional comparisons may not have a causal interpretation. [11][12][13] For example, countries that are cooler on average also tend to have higher income per capita 14 which may affect the number of new COVID-19 cases by enabling more public health measures such as testing and hospitalizations.…”
Section: Introductionmentioning
confidence: 99%